Rv0579 Is Involved in the Resistance to the TP053 Antitubercular Prodrug - Mori, Giorgia; Orena, Beatrice Silvia; Chiarelli, Laurent R.; Degiacomi, Giulia; Riabova, Olga; Sammartino, José Camilla; Makarov, Vadim; Riccardi, Giovanna; Pasca, Maria Rosalia (Frontiers in Microbiology, 2020)
Tuberculosis remains one of the leading causes of death from a single pathogen globally. It is estimated that ¼ of the world’s population harbors latent tuberculosis, but only a 5–10% of patients will develop active disease. During latent infection, Mycobacterium tuberculosis can persist unaffected by drugs for years in a non-replicating state with low metabolic activity. The rate of the successful tuberculosis treatment is curbed by the presence of these non-replicating bacilli that can resuscitate after decades and also by the spread of M. tuberculosis drug-resistant strains. International agencies, including the World Health Organization, urge the international community to combat this global health emergency. The thienopyrimidine TP053 is a promising new antitubercular lead compound highly active against both replicating and non-replicating M. tuberculosis cells, with an in vitro MIC of 0.125 g/ml. TP053 is a prodrug activated by the reduced form of the mycothiol-dependent reductase Mrx2, encoded by Rv2466c gene. After its activation, TP053 releases nitric oxide and a highly reactive metabolite, explaining its activity also against M. tuberculosis non-replicating cells. In this work, a new mechanism of TP053 resistance was discovered. M. tuberculosis spontaneous mutants resistant to TP053 were isolated harboring the mutation L240V in Rv0579, a protein with unknown function, but without mutation in Rv2466c gene. Recombineering method demonstrated that this mutation is linked to TP053 resistance. To better characterize Rv0579, the protein was recombinantly produced in Escherichia coli and a direct interaction between the Mrx2 activated TP053 and Rv0579 was shown by an innovative target-fishing experiment based on click chemistry. Thanks to achieved results, a possible contribution of Rv0579 in M. tuberculosis RNA metabolism was hypothesized, linked to toxin anti-toxin system. Overall, these data confirm the role of Rv0579 in TP053 resistance and consequently in the metabolism of this prodrug.